Evaluación de líneas diferenciales para royas (Puccinia graminis) en avena (Avena sativa L.), trigo (Triticum aestivum L.) Y cebada (Hordeum vulgare L.) del INIAP, bajo las condiciones ambientales en el campus Salache UTC 2021-2022. - Unda Palma, Jessica Fernanda (2022)
The present research work aimed to evaluate the resistance of leaf rust (Puccinia coronata) in oats (Avena sativa L.) and yellow rust (Puccinia striiformis) in wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.), in the open field conditions at the Salache Campus of the Technical University of Cotopaxi, a completely random experimental design (DCA) without repetitions was used, consisting of 52 differential lines of oats, 39 differential lines of wheat and 15 differential lines of barley, giving a total of 106 experimental units, with a total area: 47.7 m2, net area: 31.8 m2. For the evaluation of the variables under study, the methodology proposed by the INIAP (2019), called Manual No111, was applied. "Parameters of evaluation and selection in cereals" which allowed to evaluate the severity and type of reaction of the different crops under study of oats, wheat and barley, to determine the percentage of severity of leaf rust in oats and yellow rust, in wheat and barley with the following % of (5, 10, 20, 40, 60, 100), and scale for the type of reaction is Resistant (R), Moderately Resistant (MR), Moderately Susceptible (MS) and Susceptible (S). the 52 differential lines of oats, in the conditions of open field was developed until the encañado did not present incidence to the attack of rust of the leaf because no differential line survived in these conditions of open field of salache.- The results obtained of yellow rust in wheat in the differential lines with absence of the disease YR10/6*AOC, YR15/6*AOC, YRSP/6*AOC, CDCTeal, Lillian, AC Interpid, Yr43, YR5/6*AOC is due to the presence of genes resistant to yellow rust attack. The differential lines of barley with absence of yellow rust disease were: Mazurka, Bigo, I5, Bancroft of a total of 15 differential lines analyzed.